The Gains from Pension Reform - Lindbeck, Assar; Persson, Mats (Journal of Economic Literature, 2003)
We characterize pension systems along three dimensions: 1) actuarial vs. non-actuarial, 2) funded vs. pay-as-you-go, 3) defined-contribution vs. defined-benefit. Increasing the degree of actuarial fairness, by strengthening the linkage between contributions and benefits, reduces labor market distortions and may increase welfare in a Pareto-efficiency sense. Increasing the degree of funding implies mainly a redistribution of income among generations, although a partial shift to funding also provides better risk-return combinations for individuals. Shifting from defined-benefit to defined-contribution schemes (with fixed contribution rates) shifts the income risk from workers and taxpayers to pensioners.